Boolean Algebra of C-Algebras - Guddati C. Rao; Perumali Sundarayya (Journal of Mathematical and Fundamental Sciences, 2012)
A C- algebra is the algebraic form of the 3-valued conditional logic, which was introduced by F. Guzman and C.C. Squier in 1990. In this paper, some equivalent conditions for a C- algebra to become a boolean algebra in terms of congruences are given. It is proved that the set of all central elements B(A) is isomorphic to the Boolean algebra S(A) B of all C-algebras Sa, where a ïƒŽ B(A). It is also proved that B(A) is isomorphic to the Boolean algebra R(A) B of all C-algebras Aa, where a ïƒŽB(A).